Artificial Intelligence Advances for Medical Computer-Aided Diagnosis (MDPI - Multidisciplinary Digital Publishing Institute, 2024)
This Special Issue, "Artificial Intelligence Advances for Medical Computer-Aided Diagnosis," explores the transformative role of AI and ML in modern diagnostics. Featuring contributions from leading researchers, this collection highlights innovative algorithms, models, and applications that enhance diagnostic accuracy, speed, and predictive power across various medical fields, including radiology, pathology, genomics, and personalized medicine. This issue includes 12 articles, spanning theoretical advancements, algorithm development, and practical implementations, showcasing the broad impact and future potential of AI-driven diagnostics. Each contribution offers unique insights into overcoming current challenges, improving clinical decision-making, and ultimately enhancing patient outcomes. This compilation serves as a valuable resource for researchers, clinicians, and technologists, fostering further innovation and collaboration in advancing medical diagnostics. Join us in exploring the latest breakthroughs and future directions in AI-driven healthcare, as we strive to improve diagnostic accuracy and efficiency for better patient care.